2021
DOI: 10.1097/psy.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Between Oxidative Stress, Cytokines, and Psychotic Symptoms and Executive Functions in Patients With Chronic Schizophrenia

Abstract: Objective: Accumulating evidence has demonstrated that the pathophysiology of schizophrenia is involved in various abnormalities in oxidative stress markers and cytokines closely related to synaptic plasticity. However, the interactive effects among key cytokines, oxidative stress, and executive dysfunction and symptoms of schizophrenia have not been investigated yet. Methods: A total of 189 patients with chronic schizophrenia and 60 controls were recruited in the current study. Tumor necrosis factor α (TNF-α)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…Despite the heterogeneity of the findings presented, it is important to note that lipid peroxidation levels are persistently increased in the blood of chronic SZ patients, and that the TAS and the GSH blood levels are decreased ( Table 3 ). In particular, studies with more than 150 participants recruited, found that the TAS, the GPx and SOD activity were decreased in chronic SZ patients [ 24 , 25 , 26 , 27 ] ( Table 3 , Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the heterogeneity of the findings presented, it is important to note that lipid peroxidation levels are persistently increased in the blood of chronic SZ patients, and that the TAS and the GSH blood levels are decreased ( Table 3 ). In particular, studies with more than 150 participants recruited, found that the TAS, the GPx and SOD activity were decreased in chronic SZ patients [ 24 , 25 , 26 , 27 ] ( Table 3 , Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data from Wei et al ( 28 ) suggested that oxidative stress mediated particulate matter in the environment was associated with the recurrence of SCZ. On the other hand, several studies reported that natural antioxidant products such as omega-3, vitamin E and vitamin C, intervening and regulating the function of oxidation-system ( 29 , 30 ), which alleviated the symptoms of SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the oxidative/anti-oxidative status relates to clinical status of SZ is of particular interest. Numerous studies have explored the relationship between ROS and the severity of different clinical dimensions in schizophrenia (3,15), and found the complex changes of OS have been linked to cognitive impairment and psychiatric symptoms in both preclinical and clinical studies (16)(17)(18). Such as, serum SOD, GSH-Px were shown to correlate with overall severity in acute phase (19).…”
Section: Introductionmentioning
confidence: 99%